Diversity of quinoa genetic resources for sustainable production: A survey on nutritive characteristics as influenced by environmental conditions - Hlásná Cepková, Petra; Dostalíková, Lucie; Viehmannová, Iva; Jágr, Michal; Janovská, Dagmar (Frontiers in Sustainable Food Systems, 2022)
Environmental extremes and climatic variability have enhanced the changes in numerous plant stressors. Researchers have been working to improve “major” crops for several decades to make them more adaptable and tolerant to environmental stresses. However, neglected and underutilized crop species that have the potential to ensure food and nutritional security for the ever-growing global population have received little or no research attention. Quinoa is one of these crops. It is a pseudocereal, considered a rich and balanced food resource due to its protein content and protein quality, high mineral content, and health benefits. This review provides currently available information on the genetic resources of quinoa and their quality in terms of variability of economically important traits such as yield, and the content of bioactive compounds, such as protein and amino acid composition. The influence of variety and environmental conditions on selected traits is also discussed. The various types of nutrients present in the different varieties form the basis and are key for future breeding efforts and for efficient, healthy and sustainably food production.